KARAKTERISTIK FISIK TANAH PADA BEBERAPA PENGGUNAAN LAHAN DI DESA BEKA KECAMATAN MARAWOLA KABUPATEN SIGI - Bintoro, Ahmad; Widjajanto, Danang; Isrun, Isrun (AGROTEKBIS, 2017)
This study aimed to determine the characteristics of the soil under forest land, dry land, degraded land, shifting cultivation, mixed plantation, and house yards in Beka Village, Marawola Sub District of Sigi District. Three sites from each land use were determined where three soil samples were taken from each site at 0â20 cm depth using soil rings. Parameters observed included soil permeability, bulk density, porosity, water content at saturated and field capacity condition, and upper and lower plasticity limits. The soil permeability ranged from less to very fast while the soil bulk density from light to heavy. The saturated water contents were found to be 40.35% to 53.00% while the field capacity water content to be 20.18% to 26.50%. The upper and lower plasticity limits ranged from moderate to high.Â Key Words : Beka village, land use, and soil physical characteristic.